Acceptability of Naloxone Co-Prescription Among Primary Care Providers Treating Patients on Long-Term Opioid Therapy for Pain - Behar, Emily (J Gen Intern Med, 2016)
BACKGROUND: Naloxone co-prescription is recommended for patients on long-term opioids for pain, yet there are few data on the practice. OBJECTIVE: To explore naloxone co-prescribing acceptability among primary care providers for patients on long-term opioids. DESIGN: We surveyed providers at six safety-net primary care clinics in San Francisco that had initiated naloxone co-prescribing. Providers were encouraged to offer naloxone to patients on long-term opioids or otherwise at risk of witnessing or experiencing an overdose. Surveys were administered electronically 4 to 11 months after co-prescribing began. KEY RESULTS: One hundred eleven providers (69 %) responded to the survey, among whom 41.4 % were residents; 40.5 % practiced internal medicine and 55.0 % practiced family medicine. Most (79.3 %) prescribed naloxone, to a mean of 7.7 patients; 99.1 % were likely to prescribe naloxone in the future. Providers reported they were likely to prescribe naloxone to most patients, including those on low doses, defined as <20 morphine equivalent mg daily (59.8 %), ≥65 years old (83.9 %), with no overdose history (80.7 %), and with no substance use disorder (73.6 %). Most providers felt that prescribing naloxone did not affect their opioid prescribing, 22.5 % felt that they might prescribe fewer opioids, and 3.6 % felt that they might prescribe more. Concerns about providing naloxone were largely administrative, relating to time and pharmacy or payer logistics. Internists (incidence rate ratio [IRR] = 0.49, 95 % CI = 0.26–0.93, p = 0.029), those licensed for 5–20 years (IRR = 2.10, 95 % CI = 1.35–3.25, p = 0.001), and those with more patients prescribed long-term opioids (IRR = 1.10, 95 % CI = 1.05–1.14, p <0.001) were independently more likely to prescribe a greater number of naloxone compared to participants without these exposures. CONCLUSIONS: Naloxone co-prescription is considered acceptable among primary care providers. Barriers such as time and dispensing logistics may be alleviated by novel naloxone formulations intended for laypersons recently approved by the U.S. Food and Drug Administration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-016-3911-z) contains supplementary material, which is available to authorized users.